Brucellosis-induced avascular necrosis of the hip in a middle-aged person. - Sh Salarvand; Mr Nazer; Sh Shokri; S Bazhvan; Y Pournia (Tehran University of Medical Sciences, 2012)
Brucellosis is a zoonotic disease mostly transmitted to humans through consumption of unpasteurized dairy products and can lead to a systemic disease with any organ involvement. In this report, we describe a case of brucellosis-induced avascular necrosis of the hip. Brucellosis was diagnosed through serological tests, and avascular necrosis of the femoral head was confirmed by pelvic MRI. The patient was treated with a combination of antimicrobial treatments and referred to the orthopedic service for total hip arthroplasty. Brucellosis may present with unusual manifestations and should be always taken into consideration, particularly in endemic areas.